The Development of Moral Reasoning Duriung Vocational Education - Beck, Klaus [Verfasser] (My University, 1997)
"Entering vocational education can be seen as a 'status passage' from school to work. It is supposed that important life events like this status passage have a crucial and intensive impact on the development of moral judgment competence. This paper discusses the special features of the world of business with respect to its moral atmosphere and their influence on young apprentices. A distinction is made between two main types of situations, namely market situations and team situations. It is argued that the moral qualifications needed to master these situations are differing in terms of Kohlberg's theory. Data from a longitudinal study are reported. They show differences in moral judgments of the two types of situations in an unexpected direction. They also contain information on six conditions of moral development. The relation between these conditions and moral judgment competence is analyzed and it is discussed whether the findings are compatible with Kohlberg's theory of moral development." (Autorenreferat, BIBB-Doku)
Keywords: G 2.4.2 Lebenskonzepte, -stile, Werte; S 6.4.1 Kaufleute; S 1.3 Berufliche Erstausbildung; Berufsethos; Moral; Kaufmännischer Beruf; Berufsausbildung; Berufliche Sozialisation; Quantitative Angaben